UPAYA MENGURANGI TINGKAT KECEMASAN BELAJAR SISWA DALAM LAYANAN BIMBINGAN KELOMPOK - Pratama , Zikri Antoni; Rasimin, Rasimin; Yaksa, Rully Andi; Nelyahardi, Nelyahardi; Sutja, Akmal; Yusra, Affan (Yayasan Darussalam Bengkulu, 2022)
This study aims to reduce the level of student learning anxiety in Group Guidance services at SMP Negeri 8 Jambi City. The research setting is service action research (PTL) which is carried out in a systematic recycling (cycle) manner in collaboration with collaborators in a group setting. The sampling in this study used purposive sampling based on certain criteria, the subjects in this study were 8th grade students of SMP Negeri 8 who experienced learning anxiety. The data in this study were obtained through observation and interviews with students as well as directions from the BK teacher as the homeroom teacher. In this study, the final result of the group guidance service in the third cycle of the second meeting was quite satisfactory in its implementation. In its implementation, students were seen to be more relaxed and active compared to the previous cycle II, the reactions shown by students no longer showed pressure. through group guidance and question and answer services, it was found that students were able to reduce their anxiety in learning and were able to exchange their anxiety with normal feelings.